2020
DOI: 10.3892/or.2020.7745
|View full text |Cite
|
Sign up to set email alerts
|

Anti‑proliferative effect of honokiol on SW620�cells through upregulating BMP7 expression via the TGF‑β1/p53 signaling pathway

Abstract: Honokiol (HNK), a natural pharmaceutically active component extracted from magnolia bark, has been used for clinical treatments and has anti-inflammatory, antiviral and antioxidative effects. In recent years, anticancer research has become a major hotspot. However, the underlying molecular mechanisms of how HNK inhibits colorectal cancer have remained elusive. The present study focused on elucidating the effects of HNK on the expression of bone morphogenetic protein (BMP)7 and its downstream interaction with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 64 publications
(104 reference statements)
0
6
0
Order By: Relevance
“…Recent studies have found that Bone morphogenetic protein 7 (BMP7) can be produced in the salivary glands of mice [61]. Although there is no clear report on whether BMP7 is related to periodontitis and AD in the current study, related studies have proved that BMP7 be related to a variety of tumors, such as colorectal cancer [62], breast cancer [63], and prostate cancer [64].…”
Section: Discussionmentioning
confidence: 68%
“…Recent studies have found that Bone morphogenetic protein 7 (BMP7) can be produced in the salivary glands of mice [61]. Although there is no clear report on whether BMP7 is related to periodontitis and AD in the current study, related studies have proved that BMP7 be related to a variety of tumors, such as colorectal cancer [62], breast cancer [63], and prostate cancer [64].…”
Section: Discussionmentioning
confidence: 68%
“…Several studies have demonstrated that honokiol inhibits cell proliferation in colorectal cancer (Chen et al, 2004; Li et al, 2020). However, the molecular target, by which honokiol inhibits cancer cell, has remained undefined.…”
Section: Discussionmentioning
confidence: 99%
“…Honokiol is a biologically active natural compound, originally extracted from the Magnolia tree, and exerts anti‐cancer activities in a wide range of cancers including colorectal cancer, breast cancer and HNSCC (Banik et al, 2019; Ong et al, 2019; Rauf et al, 2018). Honokiol inhibits proliferation and tumour growth in colorectal cancer in vivo and in vitro (Chen et al, 2004; Li et al, 2020). In addition, honokiol can increase chemosensitization and radiosensitization of colorectal cells (He et al, 2013; Hua et al, 2013), thus representing a promising drug for treating colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The role of honokiol includes the induction of apoptosis and autophagy in osteosarcoma cells by ROS/ERK1/2 signaling [ 30 ], suppression of pancreatic cancer progression, and invasion by miR-101/Mcl-1 and SMAD2/3 axis [ 27 , 43 ], reduction of gastric tumor growth and peritoneal dissemination by inhibiting Tpl2 [ 44 ], and antagonism of doxorubicin resistance in breast cancer through miR-188-5p/FBXW7/c-Myc pathway [ 45 ]. It has also been reported that honokiol can inhibit colon cancer cell proliferation through signals such as TGF-β1/p53 [ 21 , 46 ], but only one paper revealed that the death mode induced by honokiol might be iron death [ 47 ]. Honokiol can also increase the sensitivity of tumor cells to cisplatin and oxaliplatin [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Honokiol, as one kind of polyphenol, can play an anti-tumor role through various mechanisms [ 17 ], such as antiangiogenesis [ 18 ], endoplasmic reticulum stress [ 19 ], and targeting mitochondria [ 20 ]. In colon cancer, Notch, Hippo, TGF-β, and multiple signaling pathways were considered to involve in honokiol-induced cell death [ 21 , 22 , 23 , 24 ]. However, tumors are less sensitive to honokiol than some other diseases, and the mechanisms that cause this difference remain unclear [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%